The Assessment of Blood Flow Velocities in Retinal Collaterals in Diabetic Retinopathy - Somfai, Gabor Mark; Campagnoli, Thalmon R.; Tian, Jing; Gerding, Heinrich; Smiddy, William E.; DeBuc, Delia (Klinische Monatsblätter für Augenheilkunde, 2019)
Purpose Diabetic retinopathy (DR) is a microvascular disease characterized by capillary dropout and resultant retinal ischemia which then leads to retinal vascular remodeling. Our goal was to assess blood flow velocities in retinal collateral vessels in healthy and diabetic subjects with various stages of DR.Methods In our pilot study, we enrolled five eyes of five healthy subjects (H), five eyes of four subjects with diabetes and no retinopathy (DM), three eyes of three subjects with mild non-proliferative diabetic retinopathy (MDR), and five eyes of four subjects with proliferative diabetic retinopathy (PDR). Following routine ophthalmic examination, all subjects were imaged using a retinal function imager (RFI; Optical Imaging Inc., Rehovot, Israel). The built-in software of the RFI was used to identify and segment retinal collaterals with measurement of the blood flow velocities (BFV). One-way ANOVA was performed for BFV, followed by Newman-Keuls post hoc test. The level of significance was set at 5%.Results The total number of collateral segments involved in the study was 30, 31, 21, and 39 in the H, DM, MDR, and PDR groups, respectively. The BFVs in the collaterals were significantly lower in PDR (H: 1.86 ± 0.67, DM: 1.91 ± 0.71, MDR: 1.71 ± 0.53, PDR: 1.37 ± 0.58 mm/s). The PDR group showed a statistically significant difference in the comparisons to all groups (p = 0.012, p = 0.008, and p = 0.043 for the H, DM, and MDR groups, respectively), while no other comparisons between the groups were significant.Conclusion We observed decreased BFV in retinal collaterals in PDR that may be due to the extensive capillary dropout and retinal ischemia. Further studies are needed for the noninvasive functional assessment of retinal microvascular changes in DR to better understand the underlying pathophysiology.
Keywords: retina; diabetic retinopathy; collaterals; blood flow; Retinal Function Imager